Laparoscopic cystogastrostomy - B., Niranjana P.; Mallesh, Shreya (International Surgery Journal, 2023)
Pancreatic pseudocysts (PPs) are collections of pancreatic secretions that are lined by fibrous tissues and may contain necrotic debris or blood. The interventions including percutaneous, endoscopic or surgical approaches are based on the size, location, symptoms and complications of a pseudocyst. With the availability of advanced imaging systems and cameras, better hemostatic equipment’s and excellent laparoscopic techniques, most pseudocysts can be found and managed by laparoscopy. We describe a case of a 24-year-old male patient with a pancreatic pseudocyst amenable to laparoscopic cystogastrostomy. An incision was made through the anterior gastric wall to expose the posterior gastric wall in close contact with the pseudocyst using a spinal needle aspiration guidance. Then, another incision was made for cystogastrostomy to obtain complete and unobstructed drainage. The patient recovered well after operation, suggesting that laparoscopic cystogastrostomy is a safe and effective alternative to open cystogastrostomy for minimally invasive management of pseudocyst pancreas.